Bilateral breasts metastases from gall bladder adenocarcinoma: a rare presentation - Gopal, Vaibhav Raj; Yadav, Shailendra Kumar; Ahmad, Faraz; Kumar, Surender; Shukla, Saumya; Bhargav, Mithlesh (International Surgery Journal, 2019)
Bilateral breasts metastasis from gallbladder adenocarcinoma is very rare and has never been reported. Overall incidence of breast metastasis from other primaries as reported in literature is 0.5-3%. A 38 year female presented with progressive abdominal distension followed by lumps in the left and right breasts consecutively. Abdominal examination revealed a huge right upper quadrant lump, hard in consistency and moving with respiration. CT abdomen suggested gallbladder lump infiltrating liver, colon, duodenum and pylorus. HRUSG of breasts revealed malignant lumps. Histopathology and immuno-histochemistry of breast biopsy confirmed it to be metastatic and not the primary (mammaglobin-, GATA 3 -, CK 19+, GCDFP-). Gallbladder biopsy showed adenocarcinoma with similar marker pattern. A diagnosis of gallbladder carcinoma with secondaries in bilateral breasts was made. Patient received one cycle of platinum based palliative chemotherapy and thereafter was lost to follow up. A proper clinical, radiological and histopathological examination is essential to distinguish primary and metastatic breast lesion due to the difference in the management of both. Overall prognosis is very poor and treatment should be directed towards palliative therapy of primary malignancy.